Seleksi Beberapa Varietas Padi Untuk Kuat Batang dan Ketahanan Rebah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABTRACT One of problem faced in the development of rice varieties appropriate for direct seeding method is that the varieties should have high lodging resistance. In order to study the straw strength and other related straw characters that can be used as criteria of selection for lodging resistance, a field experiment has been done in Sukamandi research station during the dry season of 2002. A total of 23 varieties were direct seeded in a randomized block design with three replications. The row spacing was 25 cm, with a planting density of 60 seeds per meter length, so that a plot consisted of 12 rows with 5 meter length, level of NPK fertilizer were (150 kg N + 50 kg P2O5 + 50- kg K20/ha), in which whole P and K, were applied in 20 days after planting and N were applied three times, 50 + 50 + 50 in 20, 55 and 65 days after planting, respectively. Variety IR-64 was used as the check The results showed that: eleven varieties gave lodging index of 1 (resistance to lodge) i.e. Cibodas, Way Seputih, Cipunegara, Citanduy, Cimandiri, Cilamaya Muncul, 1R-36, IR-42, 1R-48, IR-54 and IR-70. Modern varieties with plant height lower than 115 cm, also gave lodging index = 1 (resistance to lodging), i.e Cilamaya Muncul, Way Seputih dan Cibodas. Therefore varieties tested with plant height lower than 90 cm gave lodging index = 1 (resistance to lodge), i.e. IR-36, 1R-70 and Citanduy. Straw strength can be used as criterion of selection for high lodging resistance. Straw thickness and dry weigh of 5 cm straw section represented straw strength can be used as alternatives criteria of selection for high lodging resistance (with their respective coefficient r = 0.517* and r = 0.551*).